Chapter Le gare d'amicizia e d'amore de Arcangelo Spagna: una posible refundición de Duelo de honor y amistad - Resta, Ilaria (Studi e saggi, 2020)
This work aims to examine the adaptations of the 'comedia nueva' by Arcangelo Spagna, a Roman clergyman who lived and worked between the end of the XVII century and the first decades of the following one. In particular, we will try to verify the relationship between Spagna's comedy Le gare d'amicitia e d'amore and Herrera y Sotomayor's Duelo de honor y amistad, by examining the analogies and the differences related to this possible hypotext.